Analisis Pengaruh Variasi Komposisi Bahan Baku Terhadap Kualitas Briket Dalam Aplikasi Pembakaran - Aulia, M. Dava; Nahar, Nahar; Sariadi, Sariadi (Jurnal Riset, Inovasi, Teknologi & Terapan, 2025)
This study examines the characteristics of briquettes from the composition of coffee grounds, wood powder and coconut shells using adhesive variations. This study was designed using independent variables, namely variations in the composition of raw materials using samples (A, B, C) % and adhesives (10, 12, 15). The raw materials are carbonized at a temperature of 300°C.  The process of making briquettes begins using charcoal crushing and uniformity of charcoal particle sizes to 40/60 mesh, charcoal mixed with tapioca flour as the adhesive material, then briquette dough is formed and molded using a pressure of 7 bars and dried in an oven at a temperature of 105°C for 2 hours. Furthermore, charcoal is characterized including 5 test parameters, namely moisture content, ash content, calorific value and combustion rate, then the best results are analyzed by Thermal Gravimetry Analysis (TGA). The best results obtained from this study were in the form of B2 samples using a ratio of 35 : 65 for coffee grounds: coconut shells using an adhesive concentration of 12%. The moisture content value was 6.12%, the ash content was 6.21%, the burning rate was 0.192 grams/minute and the calorific value was 6067.03 cal/g. The results obtained in this study stated that the moisture content, ash content, and calorific value had met SNI 01-6235-2000. The conversion of the calorific value of 1 kg of arabica briquettes creates an electric power of 6,683 kWh/kg, so to get 1 kWh of electrical energy requires 0.142 kg.